Conceptions about teaching and learning of expressivity in music among Higher Education teachers and students. Issue 3 (7th April 2017) - Bonastre, Carolina; Muñoz, Enrique; Timmers, Renee
Abstract : This work aimed to analyse factors related to conceptions and beliefs about expressivity in music among students and teachers. A questionnaire with 11 Likert-type items was developed covering the main factors included in the literature of teaching-learning of expressivity and emotion in music. Through exploratory factor analysis three factors were identified: expressive technique (ET), emotional expression (EE), and self-learning of expressivity (SLE) . Comparisons between teachers and students showed that teachers had significant higher scores in EE with no differences in ET or SLE, although the effect size for SLE was high. The three factors are proposed as a tool for the assessment of conceptions of expressivity and its learning in both teachers and advanced students of music for teaching and research objectives.